Comparative mutagenic activity of atmospheric particulate matter from limeira, stockholm, and kyoto - Maselli, Bianca S.; Giron, Macelle C. G.; Lim, Hwanmi; Bergvall, Christoffer; Westerholm, Roger; Dreij, Kristian; Watanabe, Tetsushi; Cardoso, Arnaldo A. [UNESP]; Umbuzeiro, Gisela A.; Kummrow, Fábio (Wiley, 2019)
Atmospheric particulate matter (PM) organic fractions from urban centers are frequently mutagenic for the Salmonella/microsome assay. This mutagenicity is related to both primary and secondary pollutants, and meteorological conditions have great influence on the secondary pollutant's formation. Our objective was to compare the mutagenicity of atmospheric total suspended particulates (TSP) from three cities with marked different meteorological conditions and TSP concentrations: Limeira (Brazil) with 99.0 μg/m3, Stockholm (Sweden) with 6.2 μg/m3, and Kyoto (Japan) with 28.0 μg/m3. For comparison, we used the same batch of filters, sample extraction method, and Salmonella/microsome testing protocol with 11 strains of Salmonella with and without metabolic activation. Samples were collected during winter and pooled into one single extract representing each city. All samples were mutagenic for all tested strains, except for TA102. Based on the strain's selectivity, nitroarenes, polycyclic aromatic hydrocarbons, and aromatic amines play a predominant role in the mutagenicity of these samples. The mutagenic potencies expressed by mass of extracted organic material (EOM; revertants/μg EOM) were similar (~twofold difference) among the cities, despite differences in meteorological conditions and pollution sources. In contrast, the mutagenic potencies expressed by air volume (rev/m3) varied ~20-fold, with Limeira > Kyoto ≈ Stockholm. These results are the first systematic assessment of air mutagenicity from cities on three continents using the same protocols. The results confirm that the mutagenic potency expressed by EOM mass is similar regardless of continent of origin, whereas the mutagenic potency expressed by air volume can vary by orders of magnitude. Environ. Mol. Mutagen. 2019. © 2019 Wiley Periodicals, Inc.
Keywords: accelerated solvent extraction; mutagenic profiles; Salmonella/microsome microsuspension assay; total suspended particles